Wither Mario Factory?: The Role of Tools in Constructing (Co)Creative Possibilities on Video Game Consoles. (May 2013) - O'Donnell, Casey
This article examines the role that game development tools have in the design and creation of video games. It does so through the lens of a series of patents by Nintendo that outlined the technological foundations for a truly (co)creative production platform for games. Game development tools shape and are shaped by the kinds of games they are used to produce as well as the underlying technologies of game consoles. The roles, sites, and means by which users are allowed to or encouraged to engage with (co)creative tools significantly impacts the kinds of interventions users may make. The article makes the argument that tools, like Mario Factory, form a technological foundation for (co)creation, participatory design, and convergence at a level that differs significantly from the current forms.